Digital micro-mirror device -based light curing technology and its biological applications. (November 2021) - Wang, Zhen; Yang, Wenguang; Qin, Yitong; Liang, Wenfeng; Yu, Haibo; Liu, Lianqing
Highlights: The operating principles of the digital micromirror device-based printing are summarized. Chemical mechanisms of photopolymerization are reviewed. Latest advancements and applications of DMD-based printing systems are reviewed. The challenges and future directions of DMD-based printing technology for bioprinting and other applications are summarized. Abstract: 3D printing technology has significantly changed the traditional way of manufacturing mechanical structures. Digital micro-mirror-based light-curing technology provides a good way to fabricate biological as well as non-biological structures in the micro and micro-nano field because of its high resolution and efficient printing by simultaneously curing the entire layer. In biological applications, it has been possible to print biological scaffolds using this technology to precisely control the selective attachment and three-dimensional growth of cells inside the scaffold. In vitro cultured tissue models built using digital micro-mirror-based light curing technology have been used for in vitro drug screening and disease modeling. This review details the digital micromirror technique and the principles of photo-curing, as well as the basic properties of commonly used photo-curable biomaterials. The history of DMD-based light curing technology in biological applications is presented, as well as the latest developments. Finally, the outstanding challenges and development prospects of the technology are discussed.